QUALITY ASSESSMENT Of FRESH CARP (Osphronemus gouramy) WITH SOAKING CHITOSAN LIQUID - Diana Syafni; Suparmi '; Syahrul ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted the concentration of chitosan in maintaining thequality of fresh carp (Osprhonemus gouramy). The method used in this study was theexperimental method, by soaking fresh carp in a chitosan liquid 0%; 1%; 2% and 3%.Fresh carp observed to organoleptic includes eyes specification, gills, slime, meat(color and appearance), smell and texture; total plate count and total volatile base.Theresults showed the concentration of chitosan liquid could maintain the freshness ofthe fish. Treatment of 3% chitosan liquid was the best treatment. 3% chitosan liquidcould maintain the freshness of carp during to 16 hours with the value of parameterseye of 7.05; gill of 7,05); slime of 7.05; odor of 7.48; texture of 7.13; meat of 7.12; atotal of bacterial colonies of 1.99x105 colony/g; total volatile bases of 21.07 mg / 100g and pH of 5.78.Keywords: carp (Osprhonemus gouramy), chitosan, quality fresh fish